All you need to know about the music business - Passman, Donald S. 1945- (Simon & Schuster, 2015)
"For more than twenty years, All You Need to Know About the Music Business has been universally regarded as the definitive guide to the music industry. Now in its ninth edition, this latest edition leads novices and experts alike through the crucial, up-to-the-minute information on the industry's major changes in response to today's rapid technological advances and uncertain economy, "